What Is The Effect Of Sukuk On The Economic Growth Of Moslem Countries? Evidence From Oic Member Countries - Fatimah, Siti; Rahmayanti, Dini (Journal of Economics and Policy Studies (JEPS), 2023)
Economic growth is an indicator of a country's progress and a signal for the government in determining the policies that the government will undertake next. The difference in the results of previous research made the writer curious and wanted to examine this research in more detail. This study aims to data obtained from the official websites of the Worldbank, economycountry, Trading Economics, Transparency, IIFC, and UNDP. The results show that there is a long-term relationship between sukuk and crude oil prices to economic growth, which has a significant effect on the statistical value t |2.18635|, |55.3240| > critical value t |2.000995|. While the analyze the long and short-term effects of the variable sukuk, Corruption Perception Index, Human Development Index, Crude Oil Price, and economic growth in 10 member countries of the OIC for the 2017-2022 period and find out the impact and results if it occurs the effect of shocks on one variable on other variables. The method used in this study is the VECM. The data used in this study is secondary short-term relationship of the variables of sukuk and crude oil prices to economic growth also has a significant effect because of the statistical values t |2.07061|, |7.47968| > critical value t |2.000995|. Granger causality test results show that sukuk and economic growth have a two-way causality relationship. And the Granger causality test also shows that CPI, HDI, COP and economic growth do not occur in a two-way or one-way causality relationship